The Influence of Price, Product Quality, and Brand Image on the Purchase Decision of Lip Tint Implora Cosmetics - Aryani, Indah; K., Kamilah; Ikhsan Harahap, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to determine the effect of Price, Product Quality, And Brand Image on the Purchase Decision of Implora Cosmetic Liptint. In this study, a quantitative method was used with the study population consisting of Implora Cosmetic Liptint users in Mabar Hilir Village, Medan; social media users, and information about Implora Liptint products. In this study, 23 indicators were used with a sample of 100 respondents. Data were analyzed using descriptive statistical analysis to collect, manage and analyze data so that it can be presented properly describing the distribution and average frequency tables and making an analysis which states that the results are positive and influential, the coefficient of determination (R2) is obtained at 0.652, meaning that the model the coefficient of determination explains that variable (x) has an effect on variable (y). This study concludes that Price, Product Quality, and Brand Image have a significant effect on consumer Purchase Decision for Liptint Implora products partially and simultaneously.